High spatial resolution global ocean metagenomes from Bio-GO-SHIP repeat hydrography transects - Alyse A. Larkin (Nature Portfolio, 2021)
Measurement(s) DNA sequencing • temperature of water • concentration of phosphate in water • concentration of nitrogen atom in water Technology Type(s) Illumina sequencing • watercraft • continuous flow autoanalyzer Sample Characteristic - Organism marine metagenome Sample Characteristic - Environment ocean Sample Characteristic - Location global Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13971122